Communication Challenges and Supports in Pre-Employment Transition Services: Provider Perspectives. - Chang, Wen-hsuan; Zhang, Dalun; Li, Yi-Fan; Boroughani, Tahereh; Li, Peizhen; Mukherji, Sanjukta B (Journal of Vocational Rehabilitation, 2025)
Background: Employment outcomes for students with disabilities continue to lag behind those of their peers without disabilities. Although pre-employment transition services (pre-ETS) aim to improve these outcomes, communication challenges between pre-ETS providers (i.e., transition educators and vocational rehabilitation counselors) hinder effective coordination and progress. Objective: Our study investigated communication-related challenges and support among pre-ETS providers. Method: We used a qualitative approach, conducting 24 focus groups with 162 participants from six different regions across Texas, and analyzed the data using content analysis. Results: Findings revealed five primary communication-related challenges: (a) Service Eligibility and Disability Definition and Understanding, (b) Information Gaps and Exchange Issues, (c) Resource Gaps, (d) Missing Stakeholders Contact Information, and (e) Lack of Clarity Regarding Professionals' Roles and Responsibilities. In addition, we identified five primary communication-related supports: (a) Meeting Preparation, (b) Early Transition Planning, (c) Support and Resources Application, (d) Parent and Stakeholder Involvement, and (e) Integration of Educational Frameworks. Conclusion: We discussed research limitations and provided recommendations for future research and practice, to help pre-ETS providers better prepare youth with disabilities for future employment.